The Relationship Between Tahfidz Learning Strategies and Students' Academic Achievement Levels - Nur Tsani Nailal Farohah; Mulyani; Ricky Setiawan; Fiena Saadatul Ummah (Global Action and Education for Society, 2026)
This study aims to analyze the relationship between Tahfidz learning strategies and students’ academic achievement at SD Tahfidz Al-Aziz Jogotrunan Lumajang. This research employed a quantitative approach with a correlational design. The population consisted of all 80 students of SD Tahfidz Al-Aziz in the 2025/2026 academic year, while the sample included 40 third- and fourth-grade students selected using purposive sampling. Data were collected through questionnaires, observation, and documentation of students’ report scores. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test. The results showed that most students were in the high category of Tahfidz learning strategy, totaling 28 students (70.00%), and 21 students (52.50%) had high academic achievement. The Chi-Square test obtained a p-value of 0.008, indicating a significant relationship between Tahfidz learning strategies and students’ academic achievement.